Human parvovirus B19 in clotting factor concentrates: B19 DNA detection by the nested polymerase chain reaction - Zakrzewska, K; Azzi, A; Patou, G; Morfini, M; Rafanelli, D; Pattison, J R (British journal of haematology, 1992)
The presence of B19 parvovirus in plasma from blood donors is seldom demonstrable, but clotting factor concentrates, prepared from large plasma pools, may be able to transmit B19 virus infection, and the effectiveness of different chemical and physical treatment to inactivate this virus is not yet known. In this study we report on the detection of B19 DNA in 25 clotting factor concentrates, prepared by a variety of procedures of purification and inactivation; dot blot hybridization and Southern blot hybridization assays, as well as a 'nested' polymerase chain reaction (PCR) have been employed. Nine out of 25 products were B19 DNA positive by PCR, whereas only two gave positive results by hybridization techniques. B19 DNA positive concentrates have been found in 'untreated' products but also in some solvent/detergent or steam-treated products and even in monoclonal purified concentrates. PCR may be useful for the screening of blood products to be used in immunocompromised haemophiliacs, particularly in HIV positive subjects, at risk of severe chronic anaemia following B19 infection.